El legado lingüístico del fujimorismo - Lovón Cueva, Marco Antonio (2018)
Fujimorism has been studied from the spheres of politics, history and society, but not from linguistics. This research aims at describing the words that have been created in connection with Fujimorism. Since the 90s, words linked to the actions, decisions and political positions of Alberto Fujimori and his family have appeared, which have been incorporated into the popular, colloquial and standard vocabulary of Peruvians. These words are part of the linguistic memory of the speakers. This paper is a lexicographic study; therefore, it collects, lists and explains these words. Finally, this study concludes that Fujimorism has left a varied linguistic legacy in the memory of national speakers.